Miner Artist/Minor Artist? Class, Politics, and the Post-industrial Consumption of Mining Art - Spence, Jean (Frontiers in Sociology, 2020)
This article uses the recently discovered art work of a County Durham coal miner, Jimmy Kays (1886–1951) to highlight the terms in which coal mining art has achieved popularity and value in the post-mining period. Kays' work is considered with reference to the presenting narrative that promotes and markets mining art not only in terms of its intrinsic artistic quality, but also as a desirable commodity which, as a legacy of the mining past, can contribute to the revival of post-mining places. Maximizing the value that can accrue from mining art in post-industrial conditions involves appealing to the interest of the largest possible audience. The consequence of this is the dominance of a particular interpretation of the mining past. The art of Jimmy Kays does not conform to the conditions of the market, and cannot achieve a similar status. Despite its artistic qualities and its uniqueness as the product of a Durham working miner in the early twentieth century, it sits outside the dominant lexicon of coal mining art. The outsider status of Jimmy Kays is an example of a wider set of issues relating to the invisibility of working class creativity and the difficulties of achieving excellence or public acknowledgment in conditions that lack organizational support and in which value is established elsewhere. I argue that an understanding of the invisibility of art work such as that produced by Kays illuminates the exercise of class-based power in terms of the production, consumption, and range of meaning inscribed within popular mining art. Mining art that has been allocated value is in danger of being appropriated in ways that pacify rather than energize audiences, by foregrounding particular aspects of the mining past for purposes of consumption whilst submerging the issues that link more troubled aspects of the past with the present.